2016
DOI: 10.1017/s0022215116001122
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of submucosal corticosteroid injection and dilatation in subglottic stenosis of different aetiology

Abstract: Objective:To determine the long-term efficacy of submucosal corticosteroid injection plus dilatation for subglottic stenosis as a single modality treatment in granulomatosis with polyangiitis and relapsing polychondritis, as compared with idiopathic subglottic stenosis and traumatic subglottic stenosis.Method:Patients who underwent dilatation for autoimmune causes were identified. Corticosteroid injection into the submucosa of a stenotic segment was followed by serial dilatation. Definitive improvement was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
1
16
0
6
Order By: Relevance
“…Overall, 75% (3/4) of our idiopathic SGS patient were female compared to 50% (4/8) female in our intubation SGS group and a single male with Wegener's granulomatosis etiology, demonstrating a female predilection within the idiopathic cohort. The most common presenting symptom among SGS patients was dyspnea (100%), as described in prior studies …”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Overall, 75% (3/4) of our idiopathic SGS patient were female compared to 50% (4/8) female in our intubation SGS group and a single male with Wegener's granulomatosis etiology, demonstrating a female predilection within the idiopathic cohort. The most common presenting symptom among SGS patients was dyspnea (100%), as described in prior studies …”
Section: Discussionsupporting
confidence: 52%
“…Investigation of corticosteroid injections in an office‐based setting is a growing topic of interest in SGS research, as it is well tolerated and provides presumed cost‐effective advantages of nonsedation techniques, shorter procedure times, and reduced need for operative intervention with no cited adverse effects . Given the body of literature demonstrating the efficacy of intralesional corticosteroid injections in the operating room setting, the ability to provide these same injections in an office setting can revolutionize the way in which we approach clinical management of SGS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, other studies have suggested that ISI at the time of dilation in the operating room may prolong the effects of dilation in patients with GPA-related SGS/PTS. [15][16][17] More recently, the concept that serial ISI may be more effective than a single ISI in the operating room was adopted from the treatment of keloids and hypertrophic scars. 18 Serial inoffice ISI in airway stenosis were first described by Franco et al 19 and have been shown to be effective as a sole treatment strategy or as an adjunct to surgery in patients with iSGS.…”
mentioning
confidence: 99%